Análisis microbiológico de la resina de croton lechleri Müll Arg. (sangre de drago) para el consumo medicinal humano extraída de los cantones Santo Domingo, provincia de Santo Domingo de los Tsáchilas, y Pangua, Provincia de Cotopaxi - Palma Alvarado, Silvia Darling (2022)
The present investigation was carried out to determine if there is growth of pathogens in the dragon's blood resin, which poses a risk to the health of the consumer, through a microbiological analysis. The samples were obtained in two different localities Santo Domingo and Pangua in order to carry out a comparative analysis of the results obtained and determine which of the two samples presents a higher quality index for consumption, based on the Ecuadorian Technical Standard and the limits microbiological recommended by the World Health Organization regarding the maximum permissible limits to consider the level acceptable or of good quality. For this, a descriptive methodology was used, in addition, the growth of the colonies of bacteria, fungi and yeasts was highlighted and the microorganisms were identified